Rhodium(i)-catalysed cycloisomerisation/6π electrocyclisation of 5-(ethynylamino)pent-2-yn-1-yl esters to 2, 3-dihydrobenzo[f]indoles. (27th June 2022) - Merrett, James Theodore; Chen, Xiaoyu; Kyne, Sara Helen; Harode, Mandeep; Chan, Philip Wai Hong
Abstract : A rare instance in rhodium catalysis of an in situ formed rhodacycle that undergoes a formal 1, 8-acyloxy migration-initiated reductive elimination. Abstract : A synthetic method to prepare 2, 3-dihydro-1 H -benzo[ f ]indoles that relies on the rhodium(i )-catalysed cycloisomerisation/6π electrocyclisation of 5-(ethylnylamino)pent-2-yn-1-yl esters is described. The reaction mechanism was delineated to involve a rare instance in rhodium catalysis of an in situ formed rhodacycle that is susceptible to a formal 1, 8-acyloxy migration-initiated reductive elimination. This is followed by the proposed ensuing 1, 4-allenene undergoing a 6π electrocyclisation to give the N -heterocyclic product.